Social Values in Arabic Language Learning for Students at The Boarding School - Rosyada, Amrina; Muttaqin, Ichwanul; Warahmah, Mawadda (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
This study aims to determine the application of character values in Arabic language learning at Al-Ikhlas female Singosari Orphanage and Dhuafa Islamic Boarding School. It aims to determine the extent of the application of scientific integration in the teaching and learning process at the Orphan and Dhuafa Islamic Boarding School and the application of character values. This research uses qualitative research with a case study research approach. The informants in this study were female student of Al-Ikhlas female Singosari Orphanage and Dhuafa Islamic Boarding School with data collection techniques using interviews and documentation. Data analysis techniques use 3 stages, namely presenting data, reducing data, and drawing conclusions. The data validation technique uses data triangulation and theory triangulation. The results of this study are the impact of Arabic language learning at the Al-Ikhlas female Singosari Orphanage and Dhuafa Islamic Boarding School on bringing up identical social values in students, namely honesty, trustworthiness, shajaah, wadd/tarohim, and taawun.